2019
DOI: 10.1002/eap.1918
|View full text |Cite
|
Sign up to set email alerts
|

The power to detect regional declines in common bird populations using continental monitoring data

Abstract: Anthropogenic environmental change is driving the rapid loss of biodiversity. Large declines in the abundance of historically common species are now emerging as a major concern. Identifying declining populations through long‐term biodiversity monitoring is vital for implementing timely conservation measures. It is, therefore, critical to evaluate the likelihood that persistent long‐term population trends of a given size could be detected using existing monitoring data and methods. Here, we test the power to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 68 publications
(148 reference statements)
2
6
0
Order By: Relevance
“…We found that sampling effort strongly affected the ability to detect change in a timely manner, with the lowest level of sampling unable to detect change within the time tested, whereas increasing effort could potentially detect change within 13 yr for our example species. This agrees with other research showing that insufficient within-site sampling can have a large impact on the power to detect trends (e.g., Perkins et al 2016, Barker et al 2019. However, we found that increases in sampling effort in the study area with the lowest starting densities (Montara, and the reference site in particular) achieved only marginal increases in power over time, despite sites at Montara being smaller and thus the percentage area sampled with an equivalent number of transects being almost four times that of the largest sites at Bodega Head.…”
Section: Level Of Within-site Samplingsupporting
confidence: 92%
“…We found that sampling effort strongly affected the ability to detect change in a timely manner, with the lowest level of sampling unable to detect change within the time tested, whereas increasing effort could potentially detect change within 13 yr for our example species. This agrees with other research showing that insufficient within-site sampling can have a large impact on the power to detect trends (e.g., Perkins et al 2016, Barker et al 2019. However, we found that increases in sampling effort in the study area with the lowest starting densities (Montara, and the reference site in particular) achieved only marginal increases in power over time, despite sites at Montara being smaller and thus the percentage area sampled with an equivalent number of transects being almost four times that of the largest sites at Bodega Head.…”
Section: Level Of Within-site Samplingsupporting
confidence: 92%
“…The spatially and seasonally explicit trend estimates also provide new information about interannual changes in Wood Thrush population size. The spatial resolution of the trend estimates presented here is relatively high compared to other studies with similarly broad spatial extents (Sauer et al 2017, Baker et al 2019, Meehan et al 2019, Rushing et al 2019. Both breeding and non-breeding trend maps show significant spatial variation in the pattern of declines, with the steepest declines within the 5% FDR regions (Figs.…”
Section: Discussionmentioning
confidence: 55%
“…, Baker et al. , and Meehan et al. ) across broad spatial extents have turned to the use of less structured survey data collected by citizen scientists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These have been used on terrestrial as well as water birds, including waterfowls and waders. Most of the long-term studies have been conducted on North American and European birds, as a systematic census of birds is available from these regions (Baker et al, 2019;Freeman et al, 2007, Kamp et al, 2021Sauer et al, 2017;Shipley et al, 2020;Weimerskirch 2018). Painted Stork breeding population is well monitored at KNP and hence can be used to model the long-term temporal trend and effect of water availability.…”
mentioning
confidence: 99%